Internet Shutdown Policy at Papua and West Papua through the Public Policy Perspective - Irnasya Shafira Hadi; Riza Noer Arfani; Hakimul Ikhwan (Future Science, 2022)
Internet Shutdown policy implemented in August to September 2019 at Papua and West Papua has caused competing policy narrative between the government’s main narration of national security and the civil society’s contra narration of violation of human rights. This research aims to explain the Internet Shutdown policy at Papua and West Papua with public policy perspective with its main arguments hinged in human rights’ perspective. This research uses qualitative approach in which the data-gathering were done through interviews with stakeholders, documents, and media statement and analyzed using narrative policy analysis method. The result of this research shows that the polemic on Internet Shutdown in Papua happens because of the different belief systems held by the government and the civil society. The government’s belief system understands that security approach is the best approach in managing conflict in Papua, hence why Internet Shutdown is a viable way to manage said conflict. Whereas the civil society’s belief system understands that Internet Shutdown is a violation of human rights because it is harmful for the general public.